Synthesis of Fluorescent Copper Nanomaterials and Detection of Bi3+ - Wu, Rihan; Ai, Jun; Ga, Lu (Frontiers in Chemistry, 2022)
Based on the aggregation-induced luminescence of glutathione-protected non-noble metal copper nanoparticles (GSH-CuNPs), a fluorescence method for the rapid detection of bismuth (Bi3 +) was developed. The fluorescence intensity of GSH-CuNP solution is good, and the fluorescence can be quenched in the presence of Bi3 +. Based on this principle, a fluorescence mean for the admeasurement of Bi3+was built. The linear range was 0–100 mmol/L, and the detection limit was 10 mmol/L. The method is simple, rapid, and selective and can be used for the qualitative detection of Bi3 +.